BERDAK’S WORK A CLASSIC MANIFESTATION OF KARAKALPAK LITERATURE (American Journal of Technology and Applied Sciences, 2024)
This article reflects on the life and socio-political situation of the people in Berdak's works. The poet embodied in his work about the daily life of the hardworking people, the oppression of the colonists against the Karakalpak people, and the oppression of the people as a result of the unjust actions of the officials. The poet aims to develop the country by educating the youth in the spirit of patriotism.